Critical Pedagogy and the Everyday Classroom - Monchinski, Tony (Explorations of Educational Purpose,, 2008)
Critical Pedagogy addresses the shortcomings of mainstream educational theory and practice and promotes the humanization of teacher and student. Where Critical Pedagogy is often treated as a discourse of academics in universities, this book explores the applications of Critical Pedagogy to actual classroom situations. Written in a straight-forward, concise, and lucid form by an American high school teacher, drawing examples from literature, film, and, above all, the everyday classroom, this book is meant to provoke thought in teachers, students and education activists as we transform our classrooms into democratic sites. From grading to testing, from content area disciplines to curriculum planning and instruction, from the social construction of knowledge to embodied cognition, this book takes the theories behind Critical Pedagogy and illustrates them at work in common classroom environments.